MEASUREMENT OF PHYSIOGRAPHIC CHANGES ON MANGROVE-FRINGED ESTUARIES AND COASTLINES - Bird, E. C.F.; Barson, M. M. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Studies of physiographic changes are in progress on mangrove-fringed shorelines in Westernport Bay in Victoria, and Cairns Bay in Queensland, Australia. Historical evidence of advance or retreat of these shorelines has been obtained from comparison of historical maps and air photographs with the present configuration, and supplemented by monitoring shoreline